2015
DOI: 10.3389/fnins.2015.00262
|View full text |Cite
|
Sign up to set email alerts
|

Chemostimuli for guanylyl cyclase-D-expressing olfactory sensory neurons promote the acquisition of preferences for foods adulterated with the rodenticide warfarin

Abstract: Many animals have the ability to acquire food preferences from conspecifics via social signals. For example, the coincident detection of a food odor by canonical olfactory sensory neurons (OSNs) and agonists of the specialized OSNs expressing the receptor guanylyl cyclase GC-D (GC-D+ OSNs) will promote a preference in recipient rodents for similarly odored foods. It has been hypothesized that these preferences are acquired and maintained regardless of the palatability or quality of the food. We assessed whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Two choices assay and quantification of the food preference ratio. To verify if the mice display a preference between two sources of odorized food (food odor #1 or food odor #2), we adapted previously designed two choices assays [60][61][62] . In brief, grouped-housed mice were food habituated for 72 consecutive hours with access to 2 g/day/mouse of powdered ordinary food followed by 24 h of food deprivation.…”
Section: Methodsmentioning
confidence: 99%
“…Two choices assay and quantification of the food preference ratio. To verify if the mice display a preference between two sources of odorized food (food odor #1 or food odor #2), we adapted previously designed two choices assays [60][61][62] . In brief, grouped-housed mice were food habituated for 72 consecutive hours with access to 2 g/day/mouse of powdered ordinary food followed by 24 h of food deprivation.…”
Section: Methodsmentioning
confidence: 99%
“…Functional and structural studies revealed that vomeronasal receptors (VRs) respond to both pheromone and nonpheromone stimuli, for example, V2Rs respond to amino acids/peptides [4, [25][26][27][28][29], whereas TAARs detect trace amines such as p-tyramine, tryptamine, b-phenylethylamine, and octopamine [30,31]. Moreover, studies on rodent FPRs identified their potential role in detecting disease or inflammation-related ligands, while the GCs are known to be activated by membrane diffusible nitric oxide, uroguanylin, and guanylin and have also been implicated in CO 2 sensing [32][33][34][35]. All these findings collectively suggest that these structurally and functionally distinct chemoreceptor subfamilies facilitate the detection of a multitude of structurally distinct odorant molecules.…”
Section: Chemosensory Receptors Their Function and Signalingmentioning
confidence: 99%
“…Therefore, we test olfactory function and cognition by odor cross-habituation test, STFP and MWM. The odor memory is acquired in a single session and can last for weeks after training in rodents 24 26 . Lots of evidences demonstrated that the hippocampus is one of the brain regions that are implicated in the STFP.…”
Section: Discussionmentioning
confidence: 99%